Effect of different types of carbon fillers on mechanical and rheological properties of cyclic olefin copolymer (COC) composites - (:unkn) unknown (ELSEVIER SCI LTD, 2014)
In this study, morphological, mechanical and rheological properties of cycloolefin copolymer composites filled with different types of carbon fillers such as carbon black, carbon fiber, graphite and expanded graphite were investigated, in detail. Physical properties of composites were studied with the tensile test and dynamic mechanical analysis in the solid state and the theological measurements in the melt state. Aspect ratio values of graphite and expanded graphite were estimated to be about 10 and 25 with the modified-Guth model. Rheological behavior of samples indicated that the expanded graphite and carbon black dramatically increased the dynamic viscosity of composites. The intrinsic viscosity [eta] and maximum packing fraction (phi(m)) values were determined with the Krieger-Dougherty model. It was found that the [eta] values of samples prepared with the various types of fillers decreased in the order of expanded graphite > carbon black > graphite > carbonfiber. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Polymer-matrix composites (PMCs); Rheological properties; Mechanical testing; Extrusion; DENSITY POLYETHYLENE COMPOSITES; PERCOLATION-THRESHOLD; NANOTUBE COMPOSITES; TENSILE PROPERTIES; POLYMER COMPOSITE; HYBRID COMPOSITES; FIBER COMPOSITES; BIPOLAR PLATES; SOLAR-CELLS; NANOCOMPOSITES